The Structure and Function of Yemsa Adverbial Clauses: Empirical Study - M. Asrat; G. Mengistu; E. Assefa (Дискурс профессиональной коммуникации, 2024)
Yemsa, an Omotic language spoken in Ethiopia, has received limited attention in linguistic research, particularly with regard to its adverbial clauses. The lack of a comprehensive description of Yemsa’s adverbial clauses hinders our understanding of the language’s structure and its place in the Afroasiatic language family. This study aims to provide a detailed analysis of the structure and function of adverbial clauses in Yemsa, exploring their forms, functions, and subordinate markers. The research is based on a corpus of spoken and written Yemsa data, collected through fieldwork and supplemented by existing literature. A descriptive approach is employed to analyze the data, focusing on the morphological and syntactic properties of adverbial clauses. The study reveals that Yemsa adverbial clauses exhibit a range of characteristics, including dependent-person suffixes, temporal markers, and bound morphemes that connect them to main clauses. The analysis identifies five types of adverbial clauses in Yemsa: temporal, locative, manner, reason, and purpose. The findings also show that Yemsa treats aspects in adverbial clauses similarly to main clauses, with the perfective aspect remaining unmarked and the imperfective aspect marked. This research contributes significantly to our knowledge of Yemsa and the Omotic language family, providing new information about the structure and function of adverbial clauses, which is valuable for developing linguistic pedagogical materials for Yemsa. The study’s results have implications for linguistic theory, language pedagogy, and language documentation, highlighting the importance of descriptive research on understudied languages. The study’s methodology and findings can serve as a model for future research on other languages, promoting a more comprehensive understanding of linguistic diversity and complexity.